The mirage of real-time algorithmic synaesthesia: Some compositional mechanisms and research agendas in computer music and sonification. - Dean, RogerT.; Whitelaw, Mitchell; Smith, Hazel; Worrall, David (Contemporary Music Review, 2006)
This article looks at algorithmic synaesthesia, a form of sonic intermedia involving synchronous computer-mediated manipulation of sound and image. In algorithmic synaesthesia extensively shared features are created in the two media. Examples of such work by austraLYSIS and others are discussed. What an audience member can cognitively access in such synaesthesia is considered: creators of intermedia works may overestimate this. The fact that a machine can process image and sound in parallel, and by the same algorithm, does not establish that the human brain can. The transparency of an algorithmic process to a listener-viewer-screener is a core issue in auditory display (or ‘sonification’). Sonification aims to make the segmentation of a data set more accessible than it is when represented numerically or visually, and has many practical and creative applications. Current approaches in experimental cognition may assist us in evaluating these issues.